Single Cobalt Atoms Decorated N‐doped Carbon Polyhedron Enabled Dendrite‐Free Sodium Metal Anode. Issue 11 (17th September 2021) - Li, Yijuan; Xu, Pan; Mou, Jirong; Xue, Shoufeng; Huang, Shaoming; Hu, Junhua; Dong, Quanfeng; Yang, Chenghao; Liu, Meilin
Abstract: Uncontrollable growth of sodium dendrites during the sodium deposition and stripping processes remains a huge challenge for achieving high‐performance sodium metal batteries (SMBs), which results in ineffective utilization of metallic Na, low Coulombic efficiency, and inferior cycling life. Here, a single Co atom uniformly decorated porous nitrogen‐doped carbon polyhedron (CoSA @NC) matrix has been fabricated and introduced to control the Na growth and achieve uniform Na nucleation/deposition. Cryo‐electron microscopy and in situ optical microscopy techniques have been utilized to analyze the morphology change of metallic Na during plating/stripping processes. The single Co atoms evenly embedded in NC electrodes can provide stable Na‐philic sites for Na ions adsorption, which is helpful to guide the uniform sodium deposition and prevent Na dendrites growth. This work thus provides an effective solution to inhibit Na dendrite growth and control Na nucleation behavior from the perspective of atomic level, towards the fabrication of high‐safety and long‐cycling SMBs. Abstract : A single cobalt atoms‐decorated porous nitrogen‐doped carbon polyhedron (CoSA @NC) has been designed and applied as a sodium metal substrate. The single Co atom sites can provide stable Na‐philic sites for Na ions deposition with lower adsorption energy and effectively prevent the formation and growth of Na dendrites, resulting in a high sodium utilization during cycling.